Maturity and density of tertiary lymphoid structures associate with tumor metastasis and chemotherapy response - Jiang, Sutian; Liao, Xuhui; Ding, Xuzhong (Frontiers in Medicine, 2024)
Background Tertiary Lymphoid Structures (TLSs) are abnormal clusters of immune cells that form in tissues not normally associated with the immune system, usually in cases of long-lasting inflammation, like cancer. TLSs have been suggested as a potential prognostic indicator in various cancer types. Methods We retrospectively enrolled 223 gastric cancer (GC) patients who had surgical resections in this study. We utilized hematoxylin and eosin (HE) staining to detect the presence, abundance, and maturity of TLSs. In serial sections, we used immunohistochemistry to examine the cellular composition of TLSs. Results The pathological review identified TLSs in 95.1% of the tumors, lymphoid aggregates in 79.8%, primary follicles in 45.7%, and lymphoid aggregates in 95.1% of the cases. Based on Kaplan-Meier curves, the maturation and abundance of TLSs contributed to longer disease-free survival (DFS) and overall survival (OS). In addition, the density of TLSs was strongly associated with the occurrence of tumor metastases and the response to adjuvant chemotherapy. Conclusions We validated the prognostic value of TLSs in GC patients in both independent cohorts, and the maturity and density of TLS correlated with tumor metastasis. In addition, TLS may reflect sustained antitumor potency, which has important implications for adjuvant chemotherapy.